2014
DOI: 10.1002/2013jc009386
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of net heat fluxes over the Atlantic Ocean

Abstract: [1] Many studies have been undertaken to evaluate turbulent heat fluxes at the oceanatmosphere interface; less was done on the total net heat flux. We will compare heat budgets at the ocean-atmosphere interface as derived from satellites and from blended products, compare them to in situ observations, identify the location of largest differences, and attempt to explain reasons for these differences. The results over the Atlantic Sector (50 S-50 N) for a 3 year period show that differences in the turbulent flux… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 66 publications
1
41
0
Order By: Relevance
“…Using state‐of‐the‐art observations and models, we have provided statistics and patterns of the net heat budget across the surface/atmosphere interface and evaluated how accurately components of this budget can be estimated in an area of climatic significance where models encounter difficulties. We have confirmed that the net heat flux is dominated by the SW↓ radiation which also controls the latent heat flux [ Pinker et al ., ]. The SHF flux term is relatively small, so biases in its magnitude will not dominate the budget.…”
Section: Discussion and Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…Using state‐of‐the‐art observations and models, we have provided statistics and patterns of the net heat budget across the surface/atmosphere interface and evaluated how accurately components of this budget can be estimated in an area of climatic significance where models encounter difficulties. We have confirmed that the net heat flux is dominated by the SW↓ radiation which also controls the latent heat flux [ Pinker et al ., ]. The SHF flux term is relatively small, so biases in its magnitude will not dominate the budget.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…The budget equation for conservation of heat in the ocean surface mixed layer as used by Swensen and Henson [1999] is given as: Q0Qh=ρCptrue{hDHΘDt+ΔTWetrue} where Q 0 and Q h are the downward heat flux across the top and bottom of the surface mixed layer, ρ C p is the heat capacity per unit volume of seawater, h is the mixed layer thickness, Θ is the vertically averaged temperature of the mixed layer, D H / Dt is a horizontal operator, W e is the entrainment or upwelling velocity at the bottom of the mixed layer, and Δ T is the difference between Θ and the scale coverage once their credibility has been established by comparison with high quality in situ data derived from buoys or dedicated platforms. For instance, the Tropical Atmosphere Ocean (TAO) array [ McPhaden et al ., ] provides data that can be used for the calibration and validation of remotely sensed data [ Pinker et al ., ]. Subsequently, the derived estimates of the Q 0 term and its components can be used to evaluate the net surface heat flux in ocean and climate temperature just below the mixed layer.…”
Section: Introductionmentioning
confidence: 99%
“…Surface heat budget components in reanalyses are compared with more direct observations in many studies (e.g., Bosilovich et al ., ; Brunke et al ., ; Masina et al ., ; Decker et al ., ; Bosilovich et al ., ; Chaudhuri et al ., ; Dee et al ., ; Pinker et al ., ; Dolinar et al ., ; Valdivieso et al ., ). For example, Brunke et al .…”
Section: Atmospheric Reanalysesmentioning
confidence: 99%
“…Gridded ocean surface E estimates included in this study are the Objectively Analyzed air‐sea Fluxes (OAFlux version 3, Yu & Weller, , at 1° × 1° and daily resolution), the product from the SeaFlux project (SeaFlux, Clayson & Bogdanoff, ; Curry et al, , at 0.25° × 0.25° and 3‐hourly resolutions), and the product from the Institut Francais de Recherche pour l'Exploitation de la Mer (IFREMER version 4, Bentamy et al, ; Pinker et al, , at 1° × 1° and daily resolutions). All these products apply the bulk aerodynamic algorithm for computing surface latent heat flux with bulk transfer coefficients from the COARE 3.0 algorithm (Fairall et al, ), while the detailed approaches for gathering inputs for the algorithm differ among the products.…”
Section: Methodsmentioning
confidence: 99%